Tahap pencapaian pelajar dalam menyelesaikan masalah algoritma dan pemahaman konsep bagi topik stoikiometri - Omar, Siti Zubaidah (2010)
The purpose of this study was to determine students’ performance in solving algorithmic and conceptual understanding problems in school chemistry. This study was also to investigate the relationship between the students’ performances in solving algorithmic and conceptual problems. The sample of this study consisted of 120 form four science stream students from schools in Kota Tinggi, Johor. The instrument used was an open-ended questions adapted from Nakleh, (1993) and Nurrenbern & Pickering (1987). The data was analysed using Statistical Package fo r Science Social (SPSS 13.0) and presented in terms of mean and percentage. t-test and oneway ANOVA were used to analyze the differences between the groups, while the Pearson correlation was used to determine the relationship between students’ performances in solving algorithmic and conceptual problems. The findings of this study have shown that students’ performances in algorithmic is average (mean score, 50.56) while students’ performances in conceptual problems is weak (mean score, 18.89). The results also show that there was no significant difference in students’ performance in algorithmic and conceptual problems among Malay, Chinese and Indian, as well as among male and female students. Nevertheless this study shows that there was significant relationship between students’ performances in algorithmic and conceptual problem solving. Some sugesstions are recomended so that educators will be more concern of student’s performances to improve the quality of teaching and learning.